Meta-analysis of Broiler Chicken Trials Using Diets With or Without Allzyme® SSF Enzyme Complex - Hooge, D.M.; Pierce, J.L.; McBride, K.W.; Rigolin, P.J. (International Journal of Poultry Science, 2010)
A meta-analysis of body weight and feed conversion ratio results from broiler chicken pen trials plus a few commercial trials (2001-2009) from several countries was conducted to demonstrate effects of a dietary enzyme complex (Allzyme® SSF, Alltech, Inc., Nicholasville, Kentucky USA) versus no supplement (negative control) on live performance. In the statistical meta-analysis, 28 references provided results for 51 comparisons (paired t-test) from which overall averages for body weight and feed conversion ratio were calculated. The final age (days) in each trial or in the experimental feeding period was noted and an estimate of final age was calculated using the ending age in each trial. Broiler chicken final body weight with the dietary enzyme complex product was found to be 0.057 kg or 3.73% greater than unsupplemented chicken body weight whereas feed conversion ratio was lowered by 0.043 or 2.64% with the enzyme product. These changes in live performance exceed those of Fisher and Wilson (1974) and those predicted by linear regression analysis using data from Jackson et al. (1982) and Waldroup (1996) for 75 extra kcal ME/kg of diet. Therefore, the 75 kcal ME/kg uplift used in the manufacturer’s ingredient matrix appears to be conservative for the enzyme complex product based on results in the cited publications. Base on results presented herein, this enzyme complex product is recommended for use in broiler chicken feeds either by addition on top to take advantage of expected benefits or by reformulating the diets with 75 kcal less ME/kg (along with -0.1% calcium, -0.1% available phosphorus and -1% essential amino acids used in formulation). The usual rate of inclusion is 0.02% or 200 g/tonne.